ANALISIS KONTEN BUKU TEKS MATEMATIKA K-13 TERKAIT POTENSI PENGEMBANGAN LITERASI MATEMATIS - Andi Harpeni Dewantara (Didaktika : Jurnal Kependidikan, 2019)
Questions, one of the content textbook’s components, play an essential role in a learning activity. Content analysis of the textbook very important to carry out for evaluating whether the questions used in schools have an effect on the development of mathematical literacy skills as an essential ability students should acquire in the mathematics learning process. Regarding this case, this study aims to analyze the characteristics of the questions in the 2013 Curriculum (K-13) textbook related to the potential development of mathematical literacy. This research is a qualitative descriptive study using content analysis approach, investigating 135 questions in the Comparison and Scale chapter in the revised edition of the Mathematics VII grade K-13 textbook. The results of the analysis show that the questions presented do not optimally contain the components of developing students' mathematical literacy. This can be seen from the component of context usage and mathematical processes (formulate, employ, and interpret) needed to solve these problems which are not yet optimally integrated.